Juvenile Granulosa Cell Tumor of the Testis in a Newborn with Swelling in the Scrotum: A Rare Case and Literature Review - Tartar, Tugay; Sarac, Mehmet; Bakal, Unal; Canpolat, Senay; Kazez, Ahmet (Aves, 2017)
Juvenile granulosa cell tumors (JGCTs) of the testis in newborns are very rarely seen benign tumors. They occur in association with sex chromosome disorders and ambiguous genitalia. Alpha-fetoprotein levels have a poor diagnostic value for teratomas in infants < 6 months of age. Most of JGCTs are confused with a teratoma based on histopathological analysis results. Inguinal orchiectomy yields satisfactory treatment results. We present the case of our patient diagnosed with a JGCT of the testis and review the relevant literature.
Keywords: Juvenile granulosa cell tumor; testis; newborn; orchiectomy